Beyond national institutions: Labour taxes and regional unemployment in Italy - Giorgio Brunello; Claudio Lupi; Patrizia Ordine; Maria Luisa Parisi (Fondazione Eni Enrico Mattei (FEEM), 2001)
By focusing on the Italian experience, we ask whether the relationship between labour taxes and unemployment varies across regions. In spite of similar national labour market institutions, we show that this relationship is significantly stronger in the highly industrialised North than in the underdeveloped South, where unemployment is much higher. An important source of variation in the regional responsiveness of unemployment originates from the fact that regional gross wages in the North increase more than in the South in response to a hike in labour taxes. Regional wage setting affects regional employment (and unemployment) both directly and indirectly, via its impact on regional profits and the capital stock.
Keywords: J51; H20; 330; Regional unemployment; labour taxes; Regionale Arbeitslosigkeit; Lohnsteuer; Region; Regionale Lohnstruktur; Regionale Disparität; Schätzung; Italien